Psychological Distress at a Regional Australian Law School: Reporting on Law Students’ Experiences of Depression, Anxiety, and Stress - Claire Holland (Legal Education Review)
Legal education in Australia is constantly evolving to meet the needs of law students and to prepare many of them for roles in the legal profession. Examples include changes to law degree structures, optional elective units, and subjects aimed at preparing law students to be ‘workplace ready’. Law students face challenging academic requirements and law school culture that can result in greater levels of psychological distress compared to the general population. Promoting law student wellbeing and responding to high student levels of psychological distress is a key area of focus for Australian Law Schools. This article explores existing law student wellbeing studies in Australia and reports findings from an empirical exploratory study investigating the levels of depression, anxiety, and stress (DASS) using the DASS21 survey instrument in law students at a regional Australian university, James Cook University. The results from this study support earlier studies at Australian universities that show law students experience higher levels of psychological distress symptoms compared to the general population, and it is an area of concern that requires ongoing attention. Results include an exploration of the impact of factors including type of degree being studied, campus location, year of study, gender, and time spent at law school.